The Causality Relationships Between Poverty And Human Development: Empirical Evidence From Tunisia For The Period Of 1990-2017 - Belhaj, Besma; Berrek, Khadhra; Boukhris Hadda, Azhar (جامعة الوادي - University of Eloued, 2020)
Summary: This paper seeks the two objectives are to examine whether there exists any relationship between poverty and human development, and research in the direction of causality between Tunisia's these two variables from 1990 to 2017 using Toda-Yamamota Granger causality approach. The experimental results of this study showed a strong inverse relationship between the two variables and there is a one-way direction causality relationship between human development and poverty, where the Tunisian state should take some measures to avoid the phenomenon of poverty by focusing and activating programs to educate the people and promote the economy, and this is in the form of plans studied by thinkers researchers in the field of human development and the State's search for alternative short-term solutions through the development of projects.
مقال
Keywords: Human development ; Poverty ; VAR ; Toda-Yamamoto approach